Sleep disturbance as transdiagnostic mediator between adverse childhood experiences and psychopathology in children and adolescents: A structural equation modeling meta‐analysis - Jianlin Liu; Wen Lin Teh; Rachel Hsiao Shen Tan; Yoke Boon Tan; Charmaine Tang; Nisha Chandwani; Mythily Subramaniam (Wiley, 2023)
Abstract Background Increasing research efforts have focused on understanding why some individuals develop severe psychopathology after exposure to adverse childhood experiences (ACEs). Sleep disturbances (insomnia, nightmares, and sleep disorders) are prevalent sequelae of ACEs and associated with psychopathology; however, there is no meta‐analytic evidence on whether sleep disturbance functions as a transdiagnostic mediator in the relationship between ACEs and psychopathology (internalizing/externalizing disorders and psychosis) in children and adolescents. Methods Systematic searches in three databases (PubMed; PsycINFO; Web of Science) identified 98 articles (N = 402,718; age range 1-17 years) and the present study used a novel two‐stage meta‐analytic structural equation model to investigate whether ACEs predict psychopathology through sleep disturbance. Subgroup analyses determined potential biases due to study design (cross‐sectional vs. longitudinal) and geographical differences (Western vs. non‐Western countries). Sensitivity analyses evaluated the influence of early childhood (<5 years old) and overlapping symptoms (i.e., nightmares and trauma symptoms) on model stability. Results The pooled correlations among ACEs, sleep disturbance, and psychopathology were significant; the effect sizes ranged from moderate to high (r = 0.21 to r = 0.29). The indirect effect from ACEs via sleep disturbance to psychopathology was significant (β = 0.05, 95% CI [0.04, 0.06]). The direct effect of ACEs on psychopathology was significant (β = 0.18, 95% CI 0.13-0.24). Subgroup analyses revealed larger effects for cross‐sectional studies than longitudinal studies (Δ χ2 (3) = 9.71, p = 0.021). Sensitivity analyses revealed stable and consistent results. Conclusions The present meta‐analytic results indicate that sleep disturbance is a transdiagnostic mediator in the relationship between ACEs and psychopathology among children and adolescents. Further research is required to determine the synergistic effects between sleep disturbance and other risk mechanisms, and elucidate the complex pathways that lead to disorder in the aftermath of childhood adversities.